THE APPLICATIONS OF DECLARATION DECISIONS ON CIVIL PROCEDURE LAW IN INDONESIA - Zulaika, Emi; Erfandy, Noviandy Nur Fadillah Putranti; Hariyani, Iswi (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Declaratory judgment is one of the decisions that can be given by the court to confirm a pre-existing legal right or situation, and not to provide new recognition or ratification. Declaratory decisions do not require execution because the decision explains the existing situation or the actual situation. The Civil Procedure Law has not fully addressed the problems related to execution that have become complaints from the public, especially regarding the governance and execution procedures that can produce an effective and efficient process. Some of the problems that will be analyzed are whether a declaration decision can be requested for execution and find out the time limit for requesting execution of the declaration decision. Furthermore, the study will explore the broader implications of these legal gaps, such as how they contribute to delays in the resolution of disputes and the challenges faced by parties seeking justice. This lack of clear regulation significantly hinders the smooth enforcement of the judicial process and contributes to unresolved legal disputes. Juridical-normative research results in finding a legal vacuum in the regulation of execution of civil procedural law in Indonesia. In this case, it’s the declaration decision that does not need to be requested for execution, if you want to execute it, you need to file a new lawsuit. However, it should be noted that there is no provision that regulates the period of time when the decision must be executed by the losing party or the time limit for the execution of the execution decision.